Consumption Habits During the Decision Making Process in Tourism - Alexandra VINEREAN (Expert Journal of Business and Management, 2014)
It is crucial for all organizations that activate in this field to research and understand the way in which consumers make decisions and the factors that motivate and encourage tourists to make different purchases. Also, when analyzing a tourist’s consumer behavior, companies must take into consideration: the needs and patterns of the consumers, consumer preferences and requirements, tourism market segmentation, and motivational factors such as cultural, personal, emotional, status, personal development, physical, etc. In this context, this paper aims to examine the responses of 154 tourists in relation to their predisposition to purchase and the patterns that are usually decisive in the decision making process regarding tourism services.